A stiff-necked people : Palestine in jewish history - Locker, Berl (London : Victor Gollancz, 1946)
Bibliotheek Camille Huysmans
Dedicator: Locker, Berl, dedicatee: Huysmans, Camille
Engels
Monografie
Keywords: joodse staat; Palestijnse kwestie